2020
DOI: 10.21608/ejchem.2020.43946.2891
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Multi-Functional Omega-3 Oil Rich Microcapsules by Spray Drying Methodology.

Abstract: This work was proposed to prepare multi-functional omega-3 oil based microcapsules. Rosemary (Rosmarinus officianlis L.) extracts as potential active compounds were used to stabilize these omega-3 rich microcapsules against both oxidation and microbes. Solvents of different polarities as well as ultrasonic-assisted water extraction (UAE) technique were tested for preparing promising extracts. Results demonstrated that water extract showed the highest phenolic extract as well as highest radical scavenging activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…On the other hand, the predominantly saturated fatty acids composition is palmitic acid (6.04%), and stearic acid observed (5.05%). The obtained values are comparable to those in the literature, and it notes that the composition of oleic acid obtained in this work do not differ significantly from literature data, namely 20.9-24.4% and 15.81-27.99% [34], also the composition of linoleic acid, values obtained not differ much from the literature [35]. The samples of soybean oil are major unsaturated fatty acids (82.54%), while saturated fatty acids were at a rate of 17.45%.…”
Section: Fatty Acid Composition Of Oil Samples Under Investigationsupporting
confidence: 89%
“…On the other hand, the predominantly saturated fatty acids composition is palmitic acid (6.04%), and stearic acid observed (5.05%). The obtained values are comparable to those in the literature, and it notes that the composition of oleic acid obtained in this work do not differ significantly from literature data, namely 20.9-24.4% and 15.81-27.99% [34], also the composition of linoleic acid, values obtained not differ much from the literature [35]. The samples of soybean oil are major unsaturated fatty acids (82.54%), while saturated fatty acids were at a rate of 17.45%.…”
Section: Fatty Acid Composition Of Oil Samples Under Investigationsupporting
confidence: 89%
“…According to Friedt et al (1994), in addition to conventional fatty acids, sunflower oil also contains several other fatty acids, but is present only in traces (C14:0, C16:1, C14:1, C20:0, C22:0). Sunflower oil with high oleic acid content is nutritionally similar to olive oil which is considered superior to other types of seed oil (Doty, 1978;Hamed et al, 2020). Grundy (1986) and Soliman et al (2019) also suggested that a diet rich in monounsaturated fatty acids i. e. oleic acid reduces cholesterol in blood plasma (reducing the risk of coronary heart diseases), has a greater shelf life and a high degree of oxidative stability Zahran and Najafi, 2020;Farrag et al, 2020).…”
mentioning
confidence: 99%
“…However, it was specifically noted that the radical scavenging activity of ultrasonication-assisted water extract significantly increased at a temperature of 45 °C and an extraction time of 30 minutes. Additionally, it was emphasized that microcapsules prepared with the addition of rosemary using the spray drying method were better protected against oxidation (Hamed et al, 2020).…”
Section: Studies On Fish Oil Microencapsulation With Natural Extractsmentioning
confidence: 99%